PEMANFAATAN ECENG GONDOK (Eichornia crassipes) DAN PUPUK KANDANG KAMBING SEBAGAI BAHAN BAKU AMELIORAN ORGANIK - Yuliana, Anggi Indah; Ami, Mucharommah Sartika; Faizah, Mazidatul; Fithriah, Zuhriatul (Exact Papers in Compilation (EPiC), 2019)
An experiment was conducted to determine the potential of goat manure and water hyacinth plants (Eichornia crassipes) as a source of organic material (ameliorant) to improve the quality of agricultural land. Water hyacinth plants and goat manure are used as raw material for making ameliorants with various compositions, namely: 100% goat manure, 75% goat manure + 25% goiter, 50% goat manure + 50% water hyacinth, 25% manure goat + 75% water hyacinth, and 100% water hyacinth which is brooded with a time variation of 2 weeks, 4 weeks, 6 weeks and 8 weeks. The results showed that ameliorant with a high composition of goat manure had better physical quality than ameliorant which was dominated by water hyacinth. The chemical analysis showed the levels of macro nutrients (N + P2O5 + K2O) in the treatment 75% goat manure + 25% water hyacinth in 4 weeks of composting fulfilled the standard solid organic fertilizer required by Regulation of the Minister of Agriculture No. 70 of 2011 which is above 4%, while the treatment of 100% goat manure only meets the standard soil improvement material because the levels of macro nutrients (N + P2O5 + K2O) are less than 4%.